Analysis of breathing cracks using vibrations - Carr, Gustavo Eduardo (2012)
The influence of half-ellipse-shaped fatigue cracks and machined through-thickness cuts on the impact response of cantilever beam samples were analysed using the Finite Element Method and compared to experimental data for different crack depths. The effect of sample width was analysed for geometries with fatigue cracks (aspect ratio a/c = 0.45) and through-thickness cuts (rectangular cracks). The differences between both types of damage were analysed numerically and experimentally. The effect of sample width was studied and it was found that the behaviour of the cantilever with a fatigue-crack approaches that of the saw cut sample when the fatigue crack reaches the edges of the test piece. Acceleration data were analysed using the Fast Fourier Transform algorithm and Power Density Spectra (PSD) were obtained. For fatigue-cracked samples, harmonics of the frequencies of natural modes of oscillation were found. Analytical modelling was done using a mass-spring-damper system for studying the bilinear behaviour of the stiffness element. Harmonics found were assigned to the breathing behaviour of the crack. The detection threshold using frequency shifts inspection was twice as high as using spectral analysis. This would allow crack detection at half of the fatigue life of the specimen.